Law Enforcement Analysis of Recruitment Crimes with the Aim of Sexual Exploitation Based on Law Number 21 of 2007 (Study Of Verdict Number: 567/Pid.Sus/2020/Pn.Mgl) - Andre Arif Septiawan (Yayasan Mentari Madani, 2023)
Based on research and discussion then can be concluded asfollows:Factors cause perpetrator committed crime recruitment with purpose exploitation sexual in Verdict Number: 567/Pid. Sus/2020/PN.Mgl sesuai with theory factor cause occurrence criminal act ie factor internal and external. Internal factor i.e. presence impulse of in self-perpetrator for gain gain material in form money. While is factor external i.e. presence request from parties who needs service sexual to owner leased and lack of supervision in S related to existence contract that provides sexual service to guest or customer who comes or stay in rental. Enforcement law against offender offence criminal recruitment with purpose exploitation sexual based on Judgment Number: 567/Pid.Sus/2020/PN.Mgl implemented by apparatus enforcer law in framework system justice criminal, which includes investigation of which was conducted Police after received report from victim and action investigation compiled in News Event (BAP), indictment and charge against perpetrator offense criminal recruitment with purpose exploitation sexual, carried out Prosecutor's Office and set forth in letter indictment with claim law in accordance with with Article Porigin 2 Paragraph ( ) and (2) Law No. 2 Year 2007 concerning Eradication Crime Trafficking Person. Enforcement law further is conviction of crime by assembly judge. offender criminal offense recruitment with purpose sexual exploitation, i.e. with criminal imprisonment during 7 (seven) year and fine a total of Rp 20,000,000.00 (one hundred two twenty million rupiah) with provision if fine is not paid then replaced with criminal confinement during (one ) month